Does trade with multinationals induce greener production? Evidence from the Bangladesh fashion industry - Iqbal, Kazi; Mahzab, Moogdho; Motohashi, Kazuki; Takayama, Haruka (International Growth Centre, 2025)
This brief explores how responsible sourcing by multinational fashion brands improves water quality in Bangladesh’s apparel industry. Using firm-level and environmental data, the study shows that exporters working with global brands adopt greener practices, highlighting the potential of trade to drive sustainable production in developing countries.